Análise dinâmica e controle SDRE aplicado em uma reação autocatalítica com comportamento caótico - Andrade, Dana Isabelly (2025)
Understanding the dynamic behavior of bioprocesses and bioreactors is essential, as this knowledge allows the process to be optimized and parameters to be controlled for greater productivity. The master's research presented in this dissertation aimed to analyze the dynamic behavior of a bioreactor in which an autocatalytic reaction with mutation takes place, as well as to identify the regions with chaotic and periodic behavior. To do this, variations in the bioreactor's parameters were applied to determine their influence on the occurrence of chaos. To improve the model's accuracy, fractional calculus was used in the mathematical modeling of the bioreactor under study to include the memory effect in the system's dynamics. Since the reactor studied is intended to produce ethanol and increase productivity, SDRE control was also proposed to make the system operate in the region where the highest concentration of the desired product is obtained. To verify the relevance of this research, a systematic literature review was conducted using the Methodi Ordinatio methodology to identify the existing research scenario on the subject and gaps that could be filled. The numerical results showed that the system is sensitive to variation in all its parameters, which can lead the system to exhibit chaotic or periodic behavior. Using fractional order made it possible to analyze the influence of waste accumulated in processes already conducted on future results. The results also showed that the proposed control was efficient, keeping the system under control with low error and maintaining the system in the desired behavior with an accuracy of 94.12%. Analysis of the systematic literature review showed that this research contributes to the existing literature on the subject, as it was able to respond to the primary research gaps identified.